2022
DOI: 10.1002/rmb2.12462
|View full text |Cite
|
Sign up to set email alerts
|

Are tri‐pronuclear embryos that show two normal‐sized pronuclei and additional smaller pronuclei useful for embryo transfer?

Abstract: Purpose This study aimed to analyze whether tripronuclear (3PN) zygotes, with two normal‐sized PNs and an additional smaller PN (2.1PN), can be used for embryo transfer. Method(s) A retrospective embryo cohort study was conducted on 695 patients who underwent intracytoplasmic sperm injection treatment. Blastocyst formation rates were compared between 2.1PN and 2PN zygotes and PGT‐A analysis was performed on 15 blastocysts derived from 2.1PN zygotes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There was a preliminary study revealed not all morphologically 3PN embryos are genetically abnormal [26]. Some 3PN zygotes, with two normal-sized PNs and an additional smaller PN (2.1PN) embryos were diploid, however, predominantly aneuploid, and therefore could not be used for embryo transfer [27]. The de ciency of this study was that lack of analyzing the 3PN blastocysts genetic testing.…”
Section: Discussionmentioning
confidence: 96%
“…There was a preliminary study revealed not all morphologically 3PN embryos are genetically abnormal [26]. Some 3PN zygotes, with two normal-sized PNs and an additional smaller PN (2.1PN) embryos were diploid, however, predominantly aneuploid, and therefore could not be used for embryo transfer [27]. The de ciency of this study was that lack of analyzing the 3PN blastocysts genetic testing.…”
Section: Discussionmentioning
confidence: 96%
“…First, delayed blastulation (time from fading of pronuclei to blastocyst stage) occurs in embryos with multi-pronuclei (PN) in bovine models [ 95 ] and is associated with abnormal fertilization [ 96 ]. Multi-PNs in human zygotes are also associated with high rates of aneuploidy [ 97 , 98 ]. Multi-PN zygotes were not excluded from this study, and thus, the presence of multi-PN could have explained why the aged embryos had delayed blastulation.…”
Section: Discussionmentioning
confidence: 99%